2020
DOI: 10.18231/j.ijoas.2020.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of benign tumours and tumour like lesions of oral cavity

Abstract: The oral mucosa is constantly under the influence of various internal and external stimuli. It exhibits a range of developmental disorders, irritation, inflammation and neoplastic conditions. The oral cavity is the most common site for various tumours and tumour like lesions. Tumours may be benign or malignant. Various studies have been done for malignant tumours whereas very few studies have been done on benign tumours and tumour like lesions of oral cavity. 93 patients of either sex with oral cavity lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This resemblance necessitates a high index of suspicion and the routine inclusion of MEC in the differential diagnosis of persistent oral lesions, irrespective of their benign appearance. [7][8][9] Histopathologically, MEC is distinguished by its heterogenous cellular composition, including mucous, intermediate, and epidermoid cells. The presence of mitotic activity and perineural invasion, as noted in our case, indicates a more aggressive behaviour and necessitates a comprehensive treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…This resemblance necessitates a high index of suspicion and the routine inclusion of MEC in the differential diagnosis of persistent oral lesions, irrespective of their benign appearance. [7][8][9] Histopathologically, MEC is distinguished by its heterogenous cellular composition, including mucous, intermediate, and epidermoid cells. The presence of mitotic activity and perineural invasion, as noted in our case, indicates a more aggressive behaviour and necessitates a comprehensive treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings are inconsistent with the previous study reported by Ramu S et al, who observed pyogenic granulomas and fibrous epulis the most common lesions affecting males. Similarly, we applied fisher exact test where the variable values were less than 5 and the value of 1 against fisher testing represents non-significant (p=0.125) gender association focusing on Peripheral giant cell granuloma and Peripheral ossifying fibroma (Table-III) [20][21][22][23][24] . Our findings reveal that the lack of knowledge and awareness regarding periodontal care are the key factors of epulis progression.…”
Section: Discussionmentioning
confidence: 99%